Be the first to answer!
The factoring is as follows: x2 - y2 = (x + y) * (x - y)
9x squared plus 16 = 0 factored is plus and minus 4/3 i.
By factoring I get x-3 divided by x+3
3c(squared)-17c-6 = 0 (3c+1)(c-6) = 0 c= negative one third or positive 6
There is a formula for factoring the "difference of squares." In this case, the answer is (9 - 4x)(9 + 4x)
3X2 - 123(X2 - 4)=========All the factoring that can be done here.
You can use the formula for factoring the difference of two squares in this case.
Since the variable is the same, you can use the distributive property for this one. That is, subtract -8 minus 4, and attach the variable, "x", to the result.
(x-12)2 using perfect square
The discriminant of this quadratic expression is less than zero therefore it cannot be factored.
(27 x 3) - (10 x 3) = 17 x 3 = 51
You look for a common factor between the two terms, take it out, and use the distributive property.
3x squared minus 25x minus 28
2x squared minus 4
No, unless "a" happens to be equal to 0, or to 1.
-22 - -22
x3-x2 Both terms in this expression have x2 in them, so "divide" each term by it using the distributive property in reverse. x2(x-1) = x3-x2 If you "re-distribute" you should see that they are equal.
x = ? 42 = x squared minus x
2x squared minus 5x minus 3 factored is (2x+1)(x-3).
As an example, the product of (a + b) (a - b) is equal to a squared - b squared."Special product" simply means that there are special cases, when multiplying polynomials, that are worth memorizing. For example, if you know the above, then you can easily start factoring any expression that contains the difference of two perfect squares - for example, x squared minus 1, a to the power 6 minus b to the power 4, or even - if you start using complex numbers - a squared + b squared = a squared - (-1) b squared.
There are no rational factors.